2019
DOI: 10.1101/723510
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Irrelevant auditory and tactile signals, but not visual signals, interact with the target onset and modulate saccade latencies

Abstract: Saccadic eye movements bring events of interest to the center of the retina, enabling 11 detailed visual analysis. This study explored whether irrelevant auditory (experiments A, B & F), visual 12 (C & D) or tactile signals (E & F) delivered around the onset of a visual target modulates saccade 13 latency. Participants were instructed to execute a quick saccade toward a target stepping left or right 14 from a fixation position. We observed an interaction between auditory beeps or tactile vibrations 15 and the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…However, multisensory interactions are typically reported to enhance performance (Alais & Burr, 2004; Driver & Noesselt, 2008; Gondan et al, 2005; McDonald et al, 2000; Noesselt et al, 2007, 2010; Parise et al, 2012; Starke et al, 2020; Teder-Sälejärvi et al, 2005; Werner & Noppeney, 2010) which was only the case for the visual but not the auditory target in multisensory sequences. Thus, our results extend the literature of improvements of visual performance by irrelevant sounds (Maddox et al, 2015; Noesselt et al, 2010; Stein et al, 1996; Van der Burg et al, 2008; Van Vleet & Robertson, 2006; Vidal et al, 2020; Vroomen & De Gelder, 2000) by showing that such enhancement can also be achieved by asynchronously presented sounds embedded in fast stimulus sequences and when participants are oblivious about target’s modality (i.e. the multisensory sequence type was non-predictive of target’s modality).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, multisensory interactions are typically reported to enhance performance (Alais & Burr, 2004; Driver & Noesselt, 2008; Gondan et al, 2005; McDonald et al, 2000; Noesselt et al, 2007, 2010; Parise et al, 2012; Starke et al, 2020; Teder-Sälejärvi et al, 2005; Werner & Noppeney, 2010) which was only the case for the visual but not the auditory target in multisensory sequences. Thus, our results extend the literature of improvements of visual performance by irrelevant sounds (Maddox et al, 2015; Noesselt et al, 2010; Stein et al, 1996; Van der Burg et al, 2008; Van Vleet & Robertson, 2006; Vidal et al, 2020; Vroomen & De Gelder, 2000) by showing that such enhancement can also be achieved by asynchronously presented sounds embedded in fast stimulus sequences and when participants are oblivious about target’s modality (i.e. the multisensory sequence type was non-predictive of target’s modality).…”
Section: Discussionsupporting
confidence: 85%
“…To start with, a plethora of studies showed that an irrelevant stimulus can affect perception and reactions to a relevant target stimulus of a different modality (Lovelace et al, 2003; Maddox et al, 2015; Noesselt et al, 2010; Starke et al, 2020; Stein et al, 1996; Thorne & Debener, 2008; Van der Burg et al, 2008; Van Vleet & Robertson, 2006; Vidal et al, 2020; Vroomen & De Gelder, 2000). For instance, presenting an irrelevant auditory stimulus in combination with a visual target can result in increased perceived brightness of the visual target stimulus (Noesselt et al, 2008; Stein et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation